The Effect of Visual Experience on Perceived Haptic Verticality When Tilted in the Roll Plane - Cuturi, Luigi F.; Gori, Monica (Frontiers in Neuroscience, 2017)
The orientation of the body in space can influence perception of verticality leading sometimes to biases consistent with priors peaked at the most common head and body orientation, that is upright. In this study, we investigate haptic perception of verticality in sighted individuals and early and late blind adults when tilted counterclockwise in the roll plane. Participants were asked to perform a stimulus orientation discrimination tasks with their body tilted to their left ear side 90° relative to gravity. Stimuli were presented by using a motorized haptic bar. In order to test whether different reference frames relative to the head influenced perception of verticality, we varied the position of the stimulus on the body longitudinal axis. Depending on the stimulus position sighted participants tended to have biases away or towards their body tilt. Visually impaired individuals instead show a different pattern of verticality estimations. A bias towards head and body tilt (i.e. Aubert effect) was observed in late blind individuals. Interestingly, no strong biases were observed in early blind individuals. Overall, these results posit visual sensory information to be fundamental in influencing the haptic readout of proprioceptive and vestibular information about body orientation relative to gravity. The acquisition of an idiotropic vector signaling the upright might take place through vision during development. Regarding early blind individuals, independent spatial navigation experience likely enhanced by echolocation behavior might have a role in such acquisition. In the case of participants with late onset blindness, early experience of vision might lead them to anchor their visually acquired priors to the haptic modality with no disambiguation between head and body references as observed in sighted individuals (Fraser et al., 2015). With our study, we aim to investigate haptic perception of gravity direction in unusual body tilts when vision is absent due to visual impairment. Insofar, our findings throw light on the influence of proprioceptive/vestibular sensory information on haptic perceived verticality in blind individuals showing how this phenomenon is affected by visual experience.